Compliance to infection prevention and control practices for prevention of SARS-CoV-2 transmission at tertiary care hospital in North Mumbai - Patel, Kinjal; Purusottaman, Suraj; Carval, Trupti; Narvekar, Lekhan (International Journal Of Community Medicine And Public Health, 2021)
Background: Infection control practices played a major role in prevention of SARS-CoV-2 in healthcare settings. Aim of the study was to know the compliance to infection control and prevention practices by healthcare workers in COVID-19 pandemic and the measures taken for prevention of SARS-CoV-2 spread in the hospital. Methods: An observational study was conducted at tertiary care hospital for a period of one month. All healthcare workers involved in patient care of COVID-19 and non COVID-19 was observed for their infection control practices. Areas were divided in two category, intensive care unit and indoor wards for audit. Environmental samples of various surfaces from intensive care unit and wards were taken and analyzed for the presence of SARS-CoV-2 RNA by reverse transcriptase polymerase chain reaction. Results: Overall compliance to infection prevention practices were improved during pandemic. Hand hygiene compliance in intensive care unit and indoor wards of COVID-19 unit were 78.66% and 74.36% whilst in non COVID-19 units was 72.47% and 62.31% respectively. Compliance to revised biomedical waste (BMW) policy at COVID-19 unit were 85.20% and 71.49% in intensive care unit and ward respectively. However, at non COVID-19 unit, it was 65.22% and 57.60%. Nursing station and doffing area of ICU at non-COVID-19 unit showed presence of SARS-CoV-2 virus. While all samples collected from COVID-19 unit were negative. Conclusions: Infection prevention and control practices play a key role to curtail transmission of infection. Awareness among healthcare workers, hospital environment, and usage of personal protective equipment should be optimized even at non COVID-19 facility.